294 Diet nutrient digestibility and growth performance of weaned pigs fed hulled or hull-less barley differing in fermentable starch or fiber to replace wheat. (10th April 2018) - Wang, L F; Zhang, H; Beltranena, E; Zijlstra, R T
Abstract: Starch and fiber composition of whole grains may differ and thereby change site of digestion of energy-yielding nutrients from the small to large intestine. We selected 5 grains differing in fermentable carbohydrates: low-fermentable wheat (LFW); low-fermentable hulled barley (LFB); and 3 hull-less barley of moderate-fermentable (MFB), high-fermentable and high-amylose (HFA), or high-fermentable and high-β-glucan (HFB) to study apparent total tract digestibility (ATTD) of GE and CP, and DE and predicted NE value of diets. In total, 240 pigs were weaned at d 20 and fed diets containing 63.0–70.6% of the 5 grains from 1 wk post-weaning (initial BW 7.3 kg). Diets were formulated to provide 2.3 and 2.2 Mcal NE/kg, and 5.52 and 5.10 g standardized ileal digestible (SID) Lys/Mcal NE for Phase 1 (d 1–14) and Phase 2 (d 15–35), respectively. The ATTD of GE was greatest ( P < 0.05) for LFW and MFB diets (87%), intermediate for HFB and HFA diets (85%), and lowest ( P < 0.05) for LFB diet (84%) in Phase 1, with similar ranking in Phase 2 and for diet DE value. The ATTD of CP during Phase 1 was greater ( P < 0.05) for LFW diet than the 4 barley diets (85 vs. 79%), and during Phase 2 was greatest ( P < 0.05) for LFW diet (82%), intermediate for HFA and LFB diets (77%), and lowest ( P < 0.05) for MFB and HFB diets (75%). Diet predicted NE value during Phase 1 was greater ( P < 0.05) for MFB diet than the other 4 diets (2.39 vs. 2.28-2.33 Mcal/kg), and during Phase 2 was greater ( P < 0.05) for MFB (2.23 Mcal/kg) than LFB and HFB diets, and lowest for HFA diet (2.20 Mcal/kg). Overall (d 1–35), the ADFI was greatest ( P < 0.05) for LFB, LFW, and MFB diets (829-860 g), followed by HFB diet (789 g), and lowest for HFA diet (770 g). The ADG (514-557 g), but not G:F (0.64-0.67), tended to differ ( P < 0.10) among the 5 diets. In conclusion, increased fermentable carbohydrates (starch or β-glucan) or non-fermentable fiber in cereal grains reduced ATTD of energy and protein in young pigs. While increased non-fermentable fiber did not reduce growth performance, increased fermentable carbohydrates reduced ADFI. Fermentable carbohydrates should be titrated carefully in diets for young pigs to ensure that their increased inclusion does not reduce dietary energy and protein intake and thus maintains growth performance.